Effect of Cutting Frequency and Potassium Levels on Seed Yield and its Components for Berseem (Trifolium alexandrium L.) - Mahmood Abbas Abd Salama (Journal of Global Pharma Technology, 2016)
A study was conducted at one locations in the AL-Jazeera region at north of Ramadi city for winter season (2017) to investigate the affect number of cutting and different levels of potassium on seed yield and its components in berseem. Four cutting treatments (once ,twice, three and four times ) with potassium levels included (0,80,160 and 240 kg/he.-1).Were applied in a split plot design with three replication in which potassium levels were the main plots and cutting treatments were sub-plots . The results showed that significant effect on seed yield and its components, added potassium at levels (160) kg/ha produced significant higher means for all components higher seed yield (38.96 no. of seeds/flower, 2.90g. and 2.06 ton/ha.-1) was obtained from treatments received (160)kg/ha.-1 of potassium . Number of cutting stage had significant effect on seed yield and all components in winter season plants cut once gave higher seed yield (1.74 ton/ha.-1 )the 1st cut showed be don in 1st week of march . It was concluded that addition of potassium at a rate of (160) kg/ha.-1 and cut the crop four times when the 1st cut showed be done in 1st week of March gave higher seed yield of berseem.Keywords: Berseem, Cutting treatments, Potassium levels, Head length, Grain yield.